Preventing bank failure: an assessment of the risk regulatory framework for banks in Kenya - Mwangi, Gladys Wahura (Strathmore University, 2021)
Inherently, inefficient banks should be allowed to fail. However, all banks are susceptible to failure, but not all are inefficient. The failure of a bank, whether it is considered to be efficient or inefficient, may impact the stability of other banks. Thus, it is not the failure of a bank, but the impact of its failure that may be catastrophic. Such vulnerability to failure, which may considerably affect efficient banks, has promoted the concept of safe and sound banking systems in laws, regulations, and best practice principles on a national and international level. This paper discusses bank failure with a bias to Kenya. The objectives that it seeks to meet include establishing to what extent Kenya has adopted international best practice standards in the regulation of banks, analysing measures to mitigate the risk of systemic failure in Kenya’s banking industry and determining if and how Kenya’s bank regulatory framework can be improved to foster bank stability and reduce bank failures. To put it into context, the paper reflects of the history of bank failures in Kenya and briefly highlights the most recent failures of Dubai Bank, Chase Bank Limited, and Imperial Bank Limited, all of which descended into receivership from the year 2015, and some which have since been liquidated. It establishes that in all the banks, there was a violation of market conduct and some prudential requirements that banks are mandated to adhere to by legislation and the Central Bank of Kenya. Further, that Kenyan legislation and adoption of international best practice is sufficient basis for banks generally to manage their risk profiles, and for the Central Bank of Kenya to apply the necessary supervisory interventions. However, there is an opportunity to implement and enhance existing legislative provisions. The paper concludes by putting forth various recommendations towards these, all aimed at preventing bank failure.
A Thesis submitted in partial fulfillment of the requirements of the Degree of Master of Laws, at Strathmore University
Keywords: Bank failure; Risk regulatory framework; Central Bank of Kenya (CBK)